Network-based dynamic dispatching rule generation mechanism for real-time production scheduling problems with dynamic job arrivals. (February 2022) - Zhuang, Zilong; Li, Yue; Sun, Yanning; Qin, Wei; Sun, Zhao-Hui
Highlights: Network-based dynamic dispatching rule generation mechanism is established. Introducing complex network theory to extract a series of low-level heuristics. Automatic heuristic generation is formulated as a multiple attribute decision making problem. Results demonstrate the excellent performance of the proposed algorithm. Abstract: Although the concept of Industrial 4.0 has been well accepted, only few studies have dealt with real-time production scheduling of smart factories. Due to the advantages of simplicity, efficiency and quick response, heuristic rules have become the most promising technology to solve such problems. However, they suffer some drawbacks, such as high development and maintenance costs, low solution quality, and excessive emphasis on local information. To design heuristics from the perspective of system optimization and ensure the performance of heuristics in real-time production scheduling environments, this study develops a network-based dynamic dispatching rule generation mechanism. The complex network theory is introduced to extract a series of low-level heuristics from the perspective of system optimization, while the automatic heuristic generation problem is formulated as a multiple attribute decision making problem. Given that the dispersity of local features indicates their value for decision-making, the entropy weighting method is employed to automatically produce an adequate combination of the provided easy-to-implement low-level heuristics. Finally, the open shop scheduling problem with dynamic job arrivals is taken as an example to evaluate the effectiveness of the proposed algorithm. Numerical results demonstrate the excellent performance of the proposed algorithm in terms of algorithm effectiveness and computational time.